Avanços na propagação e conservação in vitro da mangabeira (Hancornia speciosa Gomes) nativa da região Nordeste. - Sá, Aline de Jesus (2009)
The mangaba tree (Hancornia speciosa Gomes) is a native plant fruit of Brazil found vegetating spontaneously in different regions of the country, from the Center-West to the North and Northeast of Brazil, which has great importance because of the use of its fruit, the mangaba, to produce pulp for use in the marketing of juices and icecreams. Because of the genetic erosion that has been observed in its natural banks of germplasm, the mangaba tree set among the species of the Northeast of Brazil who are at risk of extinction. Thus the study of alternative techniques for conservation of germplasm becomes priority to assist programs in genetic resources of the species. Another aspect to be considered is that asexual propagation methods for the variety of botanical mangaba tree the Northeast of Brazil are not defined and need to be enhanced to improve the production system and help breeding program. This study aimed to apply the techniques of tissue culture plants for asexual propagation and conservation of native populations in mangaba tree of coastal areas of northeastern of Brazil. The first chapter is a general introduction, the theoretical framework on biodiversity, sustainable development and biotechnology, genetic resources of mangaba tree in the Northeast, botanical description and occurrence, economic importance, data of the situation of production and cultivation, tissue culture plants, in vitro propagation, in vitro propagation of Hancornia speciosa Gomes and in vitro conservation. The second chapter deals with advances in in vitro propagation of mangaba tree native of the Northeast of Brazil, with the selection of best sealing bottles (threaded plastic cap, PVC film, Para-film® or aluminum foil) time of in vitro culture, explants (nodal position in the segment microcutting), culture medium and growth regulators for induction of in vitro rhizogenesis. For the in vitro multiplication cultures were maintained in MS medium with 3% sucrose and 0,6% of agar, supplemented with 1 mg.L-1 of AIA and 1 mg.L-1 of BAP and for in vitro rooting ¼ Knop's medium modified with 3% of sucrose and 0,6% of agar. The experiments were conducted in a randomized blocks design and the cultures were maintained in a growth room with temperature ranging from 26 ° C + 2 ° C, average relative humidity around 70% and photoperiod of 12 hours of cold white light (52 μmol.m-2.s-1 irradiance). The best types of fencing were the bottle of PVC film and Para-film® to the stage of establishment, Para-film® for the first subculture and PVC film and Para-film® for the second subculture. The best explants for the first subculture were the median and basal nodal segments. There was no significant effect of type of explant in the second subculture. The ideal time for the phase of establishment and the first and second subcultures was 50 days. For rooting was evaluated the effect of immersion of microcutting mangaba tree of four concentrations of a solution of IBA (0, 200, 400 and 600 mg.L-1). At 60 and 90 days of in vitro culture, was a higher numerical value for the number of roots in the presence of 400 and 600 mg.L-1 IBA. There was no significant difference in length of roots depending on the concentrations of IBA. The third chapter deals with the in vitro conservation of native mangaba tree region. The effect of mannitol in isolation and abscisic acid in interaction with different types of explants and sealing of vials in the in vitro conservation of microcutting mangaba tree. The cultures were maintained in MS medium with 3% sucrose and 0,6% of agar. The experiments were conducted in a randomized blocks design. The cultures were maintained in a growth room under the same conditions of previous experiments. Four concentrations of mannitol (0, 10, 15 and 20 g.L-1) were tested. Mannitol in the presence of the length of the shoots showed values below the control, but after 90 days of in vitro culture was observed toxic effect of mannitol in microcutting. In relation to abscisic acid, five concentrations (0; 0,5; 1,0; 2,0 and 4,0 mg.L-1) were tested in interaction with two types of sealing of bottles (threaded plastic cap and aluminum foil) and two types of explants (apical and basal microcutting). The abscisic acid (0,5 mg.L-1) showed better results for in vitro conservation of mangaba tree for a period of 90 days when microcutting of regenerated plantlets in vitro were grown in bottles sealed with aluminum foil and there was significant effect of type of explant.